Desain Sistem Informasi Penerimaan Siswa Baru Berbasis Web Dengan Google Site Terintegrasi Google Form di MA Ma’arif Cimanggu - Kuswantoro; Mochammad Hasymi Somaida; Kosim (JIQSI : Jurnal Ilmu Al Qur'an dan Studi Islam, 2023)
A computer-based system for processing student data, especially when registering and admitting new students. The current ongoing service system is still semi-computerized and each service must be run manually in the office to provide information about the required PPDB services. Due to the existence of a new student admission system, the services of the Student Admissions Committee / New Master Maarif Chimangu are provided, so this is still necessary to find solutions that can replace manual methods with already computerized ones. It's an interesting discussion. This study uses data collection techniques such as observation, interviews, and literature review to analyze the waterfall methodology, namely requirements analysis and definition, system and software design, implementation and unit testing, integration and system testing, operational and Perform maintenance and unify the modeling language. UML uses a Google Sheets database to write programs using the PHPHypertext Preprocessor programming language to describe the flow of steps, system requirements, and test methods (black box testing) in the form of objects. UML as a tool that can. As a result of the research, it was found that a new information system for student recruitment could be introduced.